ANALYSIS OF SOCIO-ECONOMIC RELATIONS OF THE ARAB COUNTRIES OF THE PERSIAN GULF WITH THE REPUBLIC OF KAZAKHSTAN (IN THE CASE OF THE UNITED ARAB EMIRATES, THE SULTANATE OF OMAN AND SAUDI ARABIA) - F.Kamoliddinov (Western European Studies, 2024)
The socio-economic relations of the Arab countries of the Persian Gulf in Central Asia, in particular with the Republic of Kazakhstan, are analyzed. After the collapse of the Union of Soviet Socialist Republics (USSR), the common cultural and religious traditions, the unity of the Muslim community, and the historical heritage motivated the development of cooperation between the countries of Central Asia and the Arabian Peninsula. The Arab countries of the Persian Gulf have the possibility of high-level financial investments, and some of these investments are used to finance the economic infrastructure projects of the republics of the Central Asian region, to develop hydrocarbon fields, as well as to invest in the banking network, especially the Islamic bank. From the point of view of economic comfort, two of the five republics in Central Asia are the most important for the Arab countries - Kazakhstan and Uzbekistan, which occupy an important geo-economic position in the Central Asian region
Keywords: diplomatic relations; trade; politics; economy